(untitled) (Research, Society and Development, 2020)
Bauhinia variegata Linn belongs to the Fabaceae family and is popularly used as a hypoglycemic agent. Phytochemical studies isolated flavonoids, terpenes, steroids and naphthalene derivatives, and for this reason, this article aims to describe the results of pharmacokinetics, toxicity and biological activities obtained in in silico studies of the isolated molecules for B. variegata. The online databases for data collection were: PreADMET and PASS online. For the design of chemical structures and physico-chemical characterization: MarvinSketch, Mcule property calculator and Chemicalize. The results suggested that Caempferol, 2’-hydroxy-4’,6’-dimethoxy-3,4-methylenedioxyhalhal, Campferol3-O-α-L-ramnoside, (2S)-5,7-dimethoxy-3’,4’-methylenedioxyflavanone and 5,6-dihydro-1,7-dihydroxy-3,4-dimethoxy-2-methyldibenz [b, f] oxepine showed a better pharmacokinetic pattern, due to the physical characteristics -chemicals are aligned with Lipinsk, however, all compounds showed inhibition on cytochrome P450 (CYP). Lupeol was the most favorable as an antineoplastic agent; β-Sitosterol and Heptatricontan-12, 13-diol antiviral capacity; flavonoids (Campferol3-O-α-L-ramnoside and 2’-hydroxy-4’,6’-dimethoxy-3,4-methylenedioxyhalhal) and Lupeol antiparasitic activity; Campferol3-O-α-L-ramnoside and Lupeol potential anti-inflammatory. The hypoglycemic action has not been found, but the hormone release pathway could be different. The compounds obtained toxic results at different trophic levels and in relation to the evaluation of carcinogenicity and mutagenicity. Based on these aspects, Campferol3-O-α-L-ramnoside and Lupeol appear to be the most promising molecules in biological activities, being able to act as antimalarials, with necessary modifications in their structure to reduce their toxic effects, as well as presenting acceptable pharmacokinetic aspects if they are candidates for drugs.